Análisis crítico jurídico sobre las implicaciones en la validez procesal de la carga probatoria para el divorcio por causal de adulterio - Pacheco Changoluisa, Luis Enrique (2025)
In Ecuador, marriage is defined as a solemn bilateral contract that unites two people; considered as a legal institution that seeks to strengthen and protect the family, since it is the basis of society and the State. This contract is based on the free will of the parties to contract it and on the fulfillment of certain obligations imposed on them by law and social morality, one of which is monogamy. Therefore, failure to comply with this obligation through the commission of the action of adultery is a failure to comply with that obligation, as it is solemn in nature and entails certain prerequisites to be met, as well as generating obligations and responsibilities, once configured in an ideal manner. Marriage has a fundamental importance for civil society, because according to the doctrine, it is the basis of Family Law by uniting two people in order to form a family; It is for this objective that this legal institution has the solemn character, which gives it certain formalities, which allow us to understand that the termination of this contract poses a certain procedure to follow. As it is a bilateral contract, if we talk about its termination, the Ecuadorian Civil Code establishes causes for its termination, the cause of Divorce being the object of study of this investigative work, specifically cause number 1 stipulated in the article. 110 of the Ecuadorian Civil Code, a cause that stipulates the adultery of one of the spouses, as a reason for the termination of the marriage through a contentious divorce, consequently the necessary tests must be carried out during the substantiation process to determine the veracity of the realization of this type of event, in which the aforementioned cause will be proven. This research analyzes the aforementioned causes, from a civil and constitutional perspective, which allows us to identify the repercussions of said cause in the current legal and social context.